Association between high-fat diet feeding and male fertility in high reproductive performance mice - Gómez Elías, Matías Daniel (2019)
The increasing worldwide prevalence of metabolic syndrome (MetS), especially in younger populations, is a risk factor for fertility disorders. However, a direct correlation of MetS with male infertility still remains unclear. In this work, we evaluated whether MetS has a negative impact on fertility of hybrid male mice with high reproductive performance. To induce a MetS-like condition, (C57BL/6xBALB/c) F1 male mice were fed a high-fat diet (HFD, 30% fat) for 19 weeks, while controls received a normal-fat diet (NFD, 6% fat). HFD-fed animals exhibited increased body weight, hypercholesterolemia, hyperglycemia and glucose intolerance. In vivo fertilisation assays performed along the treatment period showed no diferences in fertilisation nor in vitro embryo development rates between groups. While testicular weight and morphology were similar in both groups, HFD-fed mice presented lighter epididymides and higher amounts of gonadal fat. Moreover, sperm count was lower in HFD-fed mice, despite normal sperm viability, morphology, motility or acrosome reaction. Finally, no diferences were observed in in vitro fertilisation rates between groups. In summary, although HFD feeding altered some reproductive parameters, it did not impair male fertility in high performance breeders suggesting the possibility that a fertility impairment could be the result of the cumulative combination of environmental and/or genetic factors.